Alterations of muscarinic acetylcholine receptor subtypes in diffuse Lewy body disease: relation to Alzheimer's disease. Issue 2 (1st August 1999) - Shiozaki, Kazumasa; Iseki, Eizo; Uchiyama, Haruaki; Watanabe, Yasuhiro; Haga, Tatsuya; Kameyama, Kimihiko; Ikeda, Tomoaki; Yamamoto, Takayuki; Kosaka, Kenji
Abstract : OBJECTIVES: Dementia associated with Lewy bodies in cortical and subcortical areas is classified as dementia of the non-Alzheimer type and termed diffuse Lewy body disease (DLBD). The generic term "dementia with Lewy bodies (DLB)" was proposed in the international workshop on Lewy body dementia to include the similar disorders presenting Lewy bodies. In DLB, a lower level of choline acetyltransferase (ChAT) activity in the neocortex was found compared with that in Alzheimer's disease. The purpose of the present study was to determine the total amount of muscarinic acetylcholine receptors (mAChRs) and relative proportion of each subtype (m1-m4) of mAChRs in the frontal and temporal cortex of seven DLBD and 11 Alzheimer's disease necropsied brains. METHODS: A [ 3 H]quinuclidinyl benzilate (QNB) binding assay and an immunoprecipitation assay using subtype-specific antibodies were performed. Each antibody was raised against fusion proteins containing peptides corresponding to the third intracellular (i3) loops of the respective mAChR subtype. RESULTS: The total amounts of mAChRs were significantly lower in the preparations of temporal cortices from DLBD and Alzheimer's disease than in those from dead controls (seven cases). In both diseases, the proportion of the m3 receptor in the frontal cortex was significantly increased and that of the m4 receptor in the temporal cortex was significantly decreased compared with the control specimens. The proportions of the m1 and m2 subtypes were significantly different in the temporal cortex. The proportion of the m1 receptor was significantly greater in the DLBD brains, whereas that of the m2 receptor was significantly greater in the Alzheimer's disease brains than in the controls. CONCLUSIONS: The m1 receptor is the major subtype in the cerebral cortex, and m2 is known to be present at presynaptic terminals. The higher proportions of m1 in DLBD and m2 in Alzheimer's disease suggest that the manner of degeneration in the cholinergic system is different between the diseases. It is hypothesised that a severe depletion of presynaptic cholinergic projective neurons causes the upregulation of m1 receptor in the temporal cortex in DLBD.